APPRAISING NEW APPROACHES TO THE FUNDING OF TERTIARY EDUCATION FOR SUSTAINABLE NATIONAL DEVELOPMENT IN NIGERIA - Omotayo, Bolatito Abdulrafiu (Sokoto Educational Review, 2017)
This paper examined the new approaches to the funding of tertiary education for sustainable development in Nigeria. Tertiary institutions are regarded as the single most important industry for the production of high level manpower needed for the transformation of Nigerian economy and therefore deserve better funding. Tertiary institutions include Universities, Polytechnics and Colleges of Education. However, over the years, tertiary educational institutions in Nigeria have been battling with the issue of insufficient funds from its proprietors because of the insignificant percentage allocated to educational sector and this has crippled tertiary institutions in Nigeria and preventing them attaining fullest capacity, to compete with their counterparts across the globe. Low budgetary allocation to education sector, the sudden collapse of global oil market that lead to sharp reduction in government revenue, and coupled with pressure from academic staff bodies like Academic Staff Union of Universities, Academic Staff Union of Polytechnics, and Colleges of Education Academic Staff Union made government to seek for new approaches of financing tertiary education in Nigeria. This paper therefore, argues that funding of tertiary education should not be the responsibility of government alone, since education is an instrument for economic and social development; parents, educational stakeholders, private sector, employees institutions, nongovernmental organization etc have to make differential contributions to meet the cost of higher education. This paper suggested that government should collaborate with private sector, nongovernmental organizations, and International Financial Organizations such as World Bank, International Monetary Fund to fund tertiary education in Nigeria.